Mechanochromic dendrimers: the relationship between primary structure and mechanochromic properties in the bulk. Issue 48 (23rd May 2019) - Watabe, Takuma; Ishizuki, Kuniaki; Aoki, Daisuke; Otsuka, Hideyuki
Abstract : Radical-type mechanochromic dendrimers were developed and their mechano-responsivity drastically increased in higher-generation dendrimers. Abstract : Mechanochromic dendrimers (MDs) were developed as an ideal model for the elucidation of the relationship between the primary structure of molecules/macromolecules with a mechanophore. We discovered that the ratio of activated mechanophores, i.e., the performance parameter to quantitatively evaluate the mechanical response, drastically increases in higher-generation dendrimers.